Accounting Education in China: trends and perspectives after the economic reform - Niyama, Jorge Katsumi; Sales, Isabel Cristina Henrique; Rodrigues, Jomar Miranda; Oliveira, Pedro Henrique Duarte (Review of Business Management, 2007)
Since the economic reforms in the end of the 70’s, the accounting in China has been presenting a significant development, occasioning severe alterations in the country’s education system. This paper has as prior objective to present the evolution, tendencies and perspectives of the Chinese accounting education, considering pre and post-reform aspects. For that purpose, it was developed an exploratory research about the main characteristics of the Chinese education system, through a revision of the updated and specialized literature, as well as through studies on the national economic reform and its main reflexes in accounting. The aspects of the reforms in education, the curricular changes and the betterment of scientific production are presented as a way of reaching the proposed objectives. The improvement of education and the development of accounting researches are making the changes more comprehensible for the western world. Key-words: Accounting education. China. Economic reform.